Islamic identity and development : studies of the Islamic periphery - Mehmet, Ozay. (London ; New York : Routledge, 1990)
Turkey and Malaysia, two countries on the Islamic periphery, are often not included in discussions of Islamic reassertion and identity. Yet both have been at the forefront of modernization and development, and are exposed to a rising trend of Islamic revival which discloses a deep, psychological identity crisis.In Islamic Identity and Development, Ozay Mehmet examines this identity crisis in the wider context of the Islamic dilemma of reconciling nationalism with Islam. He sees the Islamic revival primarily as a protest movement, concentrated among urban migrant settlements.
pt. 1. The Islamic identity crisis -- pt. 2. The Islamic dilemma -- pt. 3. Development in the Islamic periphery : the nationalist phase -- pt. 4. Development in the Islamic periphery : the modern state and the privatization challenge -- pt. 5. Conclusion.
Includes bibliographical references (pages 236-246) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Islam -- Turkey; Islam -- Malaysia; Islam and state -- Turkey; Islam and state -- Malaysia; Islam -- Economic aspects -- Turkey; Islam -- Economic aspects -- Malaysia; Turkey -- Economic policy; Malaysia -- Economic policy; Economics -- Religious aspects -- Islam; Économie politique -- Aspect religieux -- Islam; Islam -- Aspect économique -- Turquie; Islam -- Aspect économique -- Malaisie; Islam et État -- Turquie; Islam et État -- Malaisie; Islam -- Malaisie; Asie Mineure -- Politique économique.; Malaisie -- Politique économique.; RELIGION -- Islam -- General; Economic policy; Economics -- Religious aspects -- Islam; Islam; Islam and state; Islam -- Economic aspects; Malaysia; Turkey; Islamic countries -- Economic development -- Influence of Islam